Crystal structure of ethyl (Z)-3-amino-2-cyano-3-(2-oxo-2H-chromen-3-yl)acrylate, C15H12N2O4 - Guo Chun-Mei; Chen Sha; Chu Mei-Jun; Wan Min; Nie Xu-Liang (Zeitschrift für Kristallographie - New Crystal Structures)
C15H12N2O4, monoclinic, P21/c (no. 14), a = 5.4588(5) Å, b = 29.629(3) Å, c = 8.1217(8) Å, β = 93.157(1)°, V = 1311.6(2) Å3, Z = 4, Rgt(F) = 0.0346, wRref(F2) = 0.0925, T = 296(2) K.